The Influence of Product Quality on Purchase Decision Through Brand Image: A Case Study On 3second Fashion - Nilowardono, Sengguruh; Baktiono, Agus; Artaya, I Putu; Rosyid, Amrun (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: A deep understanding of the factors influencing purchasing helps companies become more responsive, effective, and successful in marketing their products or services. This study aims to assess the impact of product quality on purchasing decisions involving the brand image factor in 3-second Fashion Surabaya. Design/methodology/approach: The research method employed a quantitative approach with the participation of 100 respondents. Structural equation model analysis was used as the analytical technique. Findings: The study results indicate that product quality influences the purchasing decisions for 3-second Fashion products. In other words, the better the product quality, the higher the consumer's decision to make a purchase. The research findings also show that brand image has an impact on purchasing decisions for 3-second Fashion products. In other words, the better the brand image, the higher the consumer's decision to make a purchase. This study also reveals that brand image serves as an intervening variable that mediates the relationship between product quality and purchasing decisions for 3-second Fashion Surabaya products. Research limitations/implications: This research focuses on the influence of product quality and brand image on purchasing decisions without considering other variables that may play a role in the purchasing process. Practical implications: Understanding the influence of product quality on purchasing decisions through the brand image in 3second Fashion Surabaya has several practical implications that can aid decision-making at the managerial and marketing levels. Practitioners and business managers can take specific steps to enhance the performance and competitiveness of the company. Originality/value: This research provides a new and original contribution, particularly regarding the relationship between product quality, brand image, and purchase decisions in the field of fashion retail. Paper type: Research paper